2016
DOI: 10.1088/1757-899x/124/1/012123
|View full text |Cite
|
Sign up to set email alerts
|

Basalt fiber insulating material with a mineral binding agent for industrial use

Abstract: The paper considers a possibility of using mining industry waste as a binding agent for heat insulating material on the basis of basalt fiber. The main objective of the research is to produce a heat-insulating material to be applied in machine building in high-temperature environments. After synthetic binder having been replaced by a mineral one, an environmentally sound thermal insulating material having desirable heat-protecting ability and not failing when exposed to high temperatures was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…To reduce the environmental stress of SCM on the ecosphere, researchers have proposed various ways to use these tailings in the building materials industry [9][10][11][12]. It is known that the pre-activated saponite-containing material is an active component in binding composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the environmental stress of SCM on the ecosphere, researchers have proposed various ways to use these tailings in the building materials industry [9][10][11][12]. It is known that the pre-activated saponite-containing material is an active component in binding composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the research, the authors showed that the binder makes it possible to produce a thermal insulation material on an industrial scale without changing the production technology of conventional mineral fibre wool. Moreover, the method of applying clay as a binder was successfully implemented in the production line at the Insulation Plant “Zavod Izolatsi” Irpen, Ukraine [ 14 ]. The second important factor affecting fibre durability is moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время базальт, обладая уникальными свойствами, применяется для производства нитей, тканей, сеток, теплоизоляционной ваты [6][7][8][9]. Активно ведутся исследования по возможности применения базальта, не перерабатывая его в волокна, в качестве дисперсного наполнителя для термо-и ректопластичных материалов [3,[9][10].…”
Section: Introductionunclassified